2009
DOI: 10.1111/j.1528-1167.2009.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete brain‐type creatine kinase deficiency in mice blocks seizure activity and affects intracellular calcium kinetics

Abstract: SUMMARYPurpose: Brain-type creatine kinase (CK-B) and ubiquitous mitochondrial creatine kinase (UbCKmit) act as components of local phosphocreatine-ATP shuttles that help in the compartmentalization and maintenance of pools of highenergy phosphate molecules in both neurons and glial cells. We investigated the role of these braintype creatine kinases during extreme energydemanding conditions in vivo (generalized tonicclonic seizures) and in vitro. Methods: The physiologic response of wild-types and mice lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Abnormal alteration of neurotransmitters levels has been found to be closely associated with many neurological diseases including epilepsy ( Huguenard, 2003 ). One of the reasons for the epileptic seizure and cognition in clinical conditions is neurotransmitter modulations by both epilepsy and AEDs ( Park and Kwon, 2008 ; Kleen et al, 2010 ). LC–MS/MS method was used to quantify the neurotransmitters simultaneously in zebrafish brain ( Santos-Fandila et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal alteration of neurotransmitters levels has been found to be closely associated with many neurological diseases including epilepsy ( Huguenard, 2003 ). One of the reasons for the epileptic seizure and cognition in clinical conditions is neurotransmitter modulations by both epilepsy and AEDs ( Park and Kwon, 2008 ; Kleen et al, 2010 ). LC–MS/MS method was used to quantify the neurotransmitters simultaneously in zebrafish brain ( Santos-Fandila et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with earlier findings that CK is crucially involved in local ATP regeneration in the vicinity of the SR Ca 2+ -ATPase pump (Rossi et al 1990), it was shown with CK knockout mice that the CK system is indeed essential for optimal refill of the SR Ca 2+ store in skeletal muscle (de Groof et al 2002). According to more recent data, CK, however, is not only important for Ca 2+ cycling in muscle, but also in the brain, as shown with brain CK knockouts, where brain Ca 2+ kinetics were affected (Streijger et al 2010). Interestingly, Cr supplementation of myogenic cells from mdx dystrophic mice improves intracellular Ca 2+ handling (Pulido et al 1998) and Cr supplementation of athletes results in shortening of muscle relaxation times in vivo, presumably by improving SR-Ca 2+ -pump function and intracellular Ca 2+ handling (van Leemputte et al 1999).…”
Section: The Ck/pcr System For Temporal and Spatial Buffering And Regmentioning
confidence: 97%
“…Moreover, it is now also appreciated that a major contribution to cognitive impairment in people with epilepsy is seizure activity, regardless of the underlying pathological cause of seizures ( Holmes, 2015 ). In fact, although it has long been acknowledged that status epilepticus or recurrent seizures can impact upon cognition, findings in both animal models and humans demonstrate that interictal spikes or IEDs can also disrupt cognitive function ( Kleen et al , 2010 , 2013 ) even if remote to the ictal onset zone ( Ung et al , 2017 ).…”
Section: Network Level Effects In Epilepsy and Dementiamentioning
confidence: 99%